O direito de arrependimento como instrumento de tutela da autonomia da vontade nos contratos de consumo - Santiago, Maria Cristina Paiva (2013)
Between the rights of the consumer stands out the importance of the “Right repentance” as an instrument of protection to manifestation of consumer’s will. The present work proposes to demonstrate the modifications that occurred on the society over the years that followed after the promulgation of the Brazilian Code of Consumer Protection. The proposal of this dissertation is to debate the rights repentance and the possibility of an extension on his field’s incidence, extending it to beyond the shops made out of the business establishment. On this purport, means that facing the positioning jurisprudential exists the possibility of the field’s of the right repentance extension for the classroom shops, what has already been made, for example on the time sharing shops.